COMPARISON OF NON CHIRPED NRZ, CHIRPED NRZ AND ALTERNATE-CHIRPED NRZ MODULATION TECHNIQUES FOR FREE SPACE OPTIC (FSO) SYSTEMS - Rezki El Arif; Sholeh Hadi Pramono; Maisara Binti Othman (Jurnal Mahasiswa TEUB, 2015)
Free Space Optics (FSO) is the technology where transmission occurs through optical waveform that contains datatransformed at the transmitter from electrical signal. Since the transmission medium of FSO is atmosphere, atmosphericscattering is the major cause for interruption of FSO link. Non return zero (NRZ) modulation is the dominant modulationscheme employed in commercial terrestrial Free Space Optic (FSO) communication systems. This research are requiredto investigate three viable modulation techniques; NRZ pulse formats, non-chirped NRZ, chirped NRZ, and alternatechirpedNRZ at 10 Gb/s and 40 Gb/s data rate. The 1550 nm of continuous wave (CW) laser is modulated with threedifferent modulation formats over 1 km of FSO channel. The signal is propogated at different attenuation value based onMalaysia weather conditions. In this paper we have successfully compared the three modulation techniques in FSOsystem due to the Malaysia weather and the performance is accessed at bit error rate (BER) of 1x10-9. The presentedsimulation of these three modulation shows that alternate-chirped NRZ has slightly better performance compared to thenon-chirped NRZ and chirped NRZ modulation format at clear weather, haze, light rain, medium rain and heavy rain.We believe that, this system is an alternative for the future optical wireless network that has a potential to be installed inthe urban and sub-urban area.Key words: Free Space Optic (FSO) Non Return Zero (NRZ) Chirping Modulation